Performance of reinforced concrete wall panel with rubber tyre as sand replacement for ibs component - Mohd Sukri Bin Zainal Abidin (School of Environmental Engineering, University Malaysia Perlis, 2014)
The objectives of this study to determine the engineering properties based on existing standards and patterns of cracking of reinforced concrete wall panel when a waste rubber tyres replace the sand in concrete mix for IBS components. Percentages of crumb rubber tyres replace sand in the reinforced concrete wall panels are 0 % (control) and 2.5 %. The size reinforced concrete wall panel sample used is 750 mm x 750 mm x 125 mm for testing the compressive strength, cube size of 100 mm x 100 mm x 100 mm used for testing the fire resistance and compressive strength test after being burned.